Pengelolaan Pariwisata Danau Napangga Berkelanjutan Oleh Bumdes Di Kabupaten Rokan Hilir - Rahmanul Rahmanul; Mayarni Mayarni (PUBLIKA : Jurnal Ilmu Administrasi Publik, 2021)
Lake tourism Napangga is a tourist destination located in Kepenghuluan Tanjung Medan, Rokan Hilir Regency. The lake which has an area of ​​296 hectares is managed by BUMDES Cahaya Napangga which was formed directly by the Kepenghuluan Tanjung Medan government. In its management, the BUMDES has several problems, namely in planning only prioritizing big events, promotions that are still micro, insufficient budget, and there is a flood disaster that inundated almost all existing facilities. The purpose of this study is to determine the sustainable management of Lake Napangga tourism in Kepenghuluan Tanjung Medan, Rokan Hilir Regency, as well as the inhibiting factors and supporting factors of sustainable Lake Napangga tourism management in Kepenghuluan Tanjung Medan, Rokan Hilir Regency. The theoretical concept used in this research is the concept of Sustainable Tourism from Muller in Kusbandrijo 2018. The methods used by researchers in this study are qualitative, and researchers conduct interviews, observations, and documentation in carrying out data collection techniques. The results obtained in this study are that the management carried out by BUMDES Cahaya Napaangga has carried out the performance according to the indicators set by the researchers, but in some cases there are still obstacles experienced by BUMDES, so that the management carried out is still not fully optimal.